2021
DOI: 10.3892/etm.2021.10757
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal flora alterations in patients with ulcerative colitis and their association with inflammation

Abstract: Ulcerative colitis (UC), which is a type of inflammatory bowel disease, is a chronic intestinal disorder of multifactorial etiology. Numerous studies have indicated an association between UC and intestinal bacteria. However, a limited number of studies regarding the expression of interleukin-17 (IL-17) and interleukin-23 (IL-23) in association with intestinal bacteria have been performed. The aim of the current study was to investigate the gut microbiota alterations in patients with UC, at a number of taxonomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 74 publications
0
18
0
Order By: Relevance
“…This randomized placebo-controlled trial could not demonstrate that butyrate supplementation is the loophole to intestinal health in persons with intestinal inflammation with the applied dose. The link between dysbiosis and intestinal inflammation is evident [39], but the causal relationships and methods to interfere with the human intestinal environment are not understood. A fiber rich diet, shifting the microbiome towards butyrate-producing bacteria may be ideal, but profound lifestyle changes are hard to realize [40].…”
Section: Discussionmentioning
confidence: 99%
“…This randomized placebo-controlled trial could not demonstrate that butyrate supplementation is the loophole to intestinal health in persons with intestinal inflammation with the applied dose. The link between dysbiosis and intestinal inflammation is evident [39], but the causal relationships and methods to interfere with the human intestinal environment are not understood. A fiber rich diet, shifting the microbiome towards butyrate-producing bacteria may be ideal, but profound lifestyle changes are hard to realize [40].…”
Section: Discussionmentioning
confidence: 99%
“…Gut microbiota plays an important role in the pathogenesis, development, and recovery of UC. Related studies have shown that the change of gut microbiota in patients with UC is closely related to the degree of inflammation ( Dai et al, 2021 ).…”
Section: The Potential Mechanisms Of Macrophage Polarization Regulate...mentioning
confidence: 99%
“…UC pathogenesis is the result of a combination of multiple pathogenic factors, and diffuse mucosal inflammation is the main symptom ( Dai et al., 2021 ). Recent studies have found the abnormal production of inflammatory cytokines and activation of related signaling pathways in individuals with T2DM, and gut-microbiota disorders and intestinal-barrier injury both play important roles in the pathological process of inflammation, similar to that in UC ( Hotamisligil, 2006 ).…”
Section: The Relationship Between Uc and T2dmmentioning
confidence: 99%